Agnes Kovacs' Full Stroke at 120 m of Her 200 m Breaststroke Gold Medal Race at the 1998 Perth World Championships - Rushall, B. S. (1999)
Video pictures (25 frames) and the appropriate technical/ biomechanical explanations for Agnes Kovacs' Full Stroke at 120 m of Her 200 m Breaststroke Gold Medal Race at the 1998 Perth World Championships. This stroke shows minimal effective outsweep and insweep. Arm propulsion is primarily a "butterfly-type pull" with a backward force being created through upper arm adduction. The speed and directness of the kick is particularly efficient and effective. This swimmer does not display many of the traditional concepts of breaststroke. She displays a direct propulsive arm pull as opposed to a "lift-oriented" lateral sweeping arm action. The slowing of the hands under the neck while breathing is one feature could be improved.